Cultural Acculturation in the Architecture of the Kudus Tower Mosque: A Study of Art Semiotics - Sutarjo, Johan; Eko Haryanto; Rahina Nugrahani; Widodo Widodo; Slamet Haryono (Universitas Negeri Semarang, 2024)
This study examines the process of cultural acculturation reflected in the architecture of the Al-Aqsa Menara Kudus Mosque using an art semiotic approach. This mosque is real evidence of the harmony of Hindu, Buddhist, and Islamic cultures in Java during the spread of Islam. Architectural elements such as towers that resemble Hindu-Buddhist temples, lotus flower ornaments, and Islamic calligraphy reflect an inclusive and adaptive blend of cultures. This study uses a descriptive-analytical method based on case studies by combining primary data through direct observation and interviews, as well as secondary data from related literature. Semiotic analysis was carried out to identify the symbolic meaning in the architectural elements of the mosque, with the theoretical approach of Charles Sanders Peirce and Roland Barthes. The results of the study also explain that the Menara Kudus Mosque not only functions as a place of worship, but also as a symbol of cultural identity that emphasizes harmony in diversity. This acculturation process reflects the success of Islam in adapting local traditions without eliminating original cultural values. This study makes an important contribution to understanding cultural integration in architectural art and the preservation of local cultural heritage.